Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/jnc.14642
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum stress is transmissible in vitro between cells of the central nervous system

Abstract: Improper protein folding and trafficking are common pathological events in neurodegenerative diseases that result in the toxic accumulation of misfolded proteins within the lumen of the endoplasmic reticulum (ER). While low-level stimulation of the unfolded protein response (UPR) is protective, sustained UPR activation resulting from prolonged ER stress can promote neurotoxicity. The cell-autonomous mechanisms of the UPR have been extensively characterized. However, the cellextrinsic role of the UPR under phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 42 publications
1
18
0
Order By: Relevance
“…S1b,e and S2b) as well as acceptor cells (Fig. S1c,f and S2c), reproducing the published results obtained using tumor cells and macrophages (Mahadevan et al ) and neuronal cells (Sprenkle et al, ). However, whereas UPR activation increased over time in donor cells, the CM‐induced UPR activation in acceptor cells at 1 h reached maximum levels and did not show this increase at subsequent time points (Fig.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…S1b,e and S2b) as well as acceptor cells (Fig. S1c,f and S2c), reproducing the published results obtained using tumor cells and macrophages (Mahadevan et al ) and neuronal cells (Sprenkle et al, ). However, whereas UPR activation increased over time in donor cells, the CM‐induced UPR activation in acceptor cells at 1 h reached maximum levels and did not show this increase at subsequent time points (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Transmission of full UPR signaling, that is, activation of all three branches of the UPR, has been reported in cell models using transfer of conditioned media (CM) of tumor cells subjected to ER stress, to unstressed macrophages (Mahadevan et al ). A similar model in neuronal cells and astrocytes also showed transmission of the signaling by all UPR branches (Sprenkle et al, ). In agreement with the danger signaling hypothesis, CM treatment resulted in resistance to subsequent ER stress in these cell‐to‐cell transmission models (Rodvold et al ; Sprenkle et al, ).…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…For instance, Zhang et al [10] demonstrated that the ER stress present in infected cardiomyocytes was able to transmit both the ER stress and pro-inflammatory properties into macrophages via soluble molecules but cell-cell contacts were not involved. In addition, ER stress can be transmitted between astrocytes, neurons, and microglia through soluble molecules in culture conditions [116]. It is known that ROS compounds and inflammatory mediators, e.g., IL-1β, TNF-α, and HMGB1, are able to induce ER stress in several nonimmune cells [117][118][119].…”
Section: Inflamed Microenvironment Provokes Immunosuppressionmentioning
confidence: 99%
“…Different studies suggested that the activation of all three branches of the UPR is transmissible from tumor cells (donors) in which ER stress was induced by using compounds to unstressed macrophages (acceptors) via conditioned media (CM) [ 70 ]. These results have been replicated in an additional tumor cell line combined with macrophages [ 71 ] and also in other cell types, including hepatocytic donor cells and macrophages [ 72 ] and neuronal cells and glia cells [ 73 ], all using a similar protocol. However, data from our group demonstrate that this compound-based UPR transmission protocol [ 70 , 71 , 72 , 73 ] is not suitable to study UPR transmission [ 50 ].…”
Section: Cell Non-autonomous Upr Signalingmentioning
confidence: 76%